2012
DOI: 10.1123/pes.24.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Redesigned Outdoor Space on Preschool Children’s Physical Activity During Recess

Abstract: This study investigated the impact of renovation and redesign of a university preschool's outdoor space on children's sedentary behavior, light activity, and moderate-to-vigorous-physical-activity (MVPA) during unstructured recess. Physical activity was measured by accelerometry and direct observation in two independent samples of 50 (baseline) and 57 (postintervention) children (Mage = 4.4 yrs ± 0.5). Controlling for gender, age, BMI and recess length, observational data, but not accelerometry, revealed a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
0
32
0
2
Order By: Relevance
“…Research shows that the presence of portable play equipment may increase children's PA, while fixed play structures may inhibit activity. 17,[22][23][24][25] However, a recent study suggests there is some evidence to the contrary. 30 Nonprofit centers were also more likely to have an indoor play area within the center.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Research shows that the presence of portable play equipment may increase children's PA, while fixed play structures may inhibit activity. 17,[22][23][24][25] However, a recent study suggests there is some evidence to the contrary. 30 Nonprofit centers were also more likely to have an indoor play area within the center.…”
Section: Discussionmentioning
confidence: 86%
“…20 Modifiable playground characteristics, equipment use, and equipment availability were also related to the PA levels of young children. 17,[21][22][23][24][25] A few studies have compared characteristics of the child care environment to national PA recommendations. Using an observational instrument to measure child care practices and environmental characteristics in North Carolina centers, McWilliams et al 26 found that 13% of centers provided children with at least 120 minutes of PA daily.…”
mentioning
confidence: 99%
“…Research shows that the presence of portable play equipment may increase children’s PA, while fixed play structures may inhibit activity. 17,2225 However, a recent study suggests there is some evidence to the contrary. 30 Nonprofit centers were also more likely to have an indoor play area within the center.…”
Section: Discussionmentioning
confidence: 99%
“…20 Modifiable playground characteristics, equipment use, and equipment availability were also related to the PA levels of young children. 17,2125 …”
mentioning
confidence: 99%
“…Most of the studies have been short term (less than 14 weeks), and follow-up has been rare or non-existent. There have been attempts to transfer the associations shown in cross-sectional studies between children's PA levels and outdoor time [23] to intervention programs, but these have met with mixed results [24][25][26][27][28][29]. In addition to the policies and practices of the childcare centers, the influence of teachers on children's PA levels has been recognized [19,30], and so teachers are often essential targets for the intervention.…”
Section: Material/methodsmentioning
confidence: 99%